2018
DOI: 10.1093/infdis/jiy119
|View full text |Cite
|
Sign up to set email alerts
|

Divergent preS Sequences in Virion-Associated Hepatitis B Virus Genomes and Subviral HBV Surface Antigen Particles From HBV e Antigen-Negative Patients

Abstract: Differences in composition of SVPs may result in genotype-specific immunogenicity and pathogenesis. In the patients with preS-mutations, secreted HBsAg and released viral genomes cannot be derived from the same genetic source. As viral genomes are derived from covalently closed circular DNA (cccDNA), HBsAg is presumably derived from integrated DNA. This important HBsAg source should be considered for novel antiviral strategies in HBeAg-negative chronic HBV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 24 publications
3
37
1
Order By: Relevance
“…Quantification of the semi-en- HBsAg-specific antibodies did not show truncated LHBs, presumably due to the transcomplementation from integrated HBV-DNA. 47 Expression of this mutant shows no intracellular HBsAg retention but higher level of HBsAg secretion, which differs from effects of C-terminal mutations in PreS1 on HBsAg production and secretion. [13][14][15]21,23 In general, selective overexpression of LHBs causes the intracellular retention of HBsAg in the ER 48,49 A more detailed analysis revealed that N-terminal residues from aa 6 to aa 19 in the PreS1 domain were responsible for its ER retention.…”
Section: Deletion Of Aa 25-39 In the Pres1 Domain Is A Causative Famentioning
confidence: 86%
See 2 more Smart Citations
“…Quantification of the semi-en- HBsAg-specific antibodies did not show truncated LHBs, presumably due to the transcomplementation from integrated HBV-DNA. 47 Expression of this mutant shows no intracellular HBsAg retention but higher level of HBsAg secretion, which differs from effects of C-terminal mutations in PreS1 on HBsAg production and secretion. [13][14][15]21,23 In general, selective overexpression of LHBs causes the intracellular retention of HBsAg in the ER 48,49 A more detailed analysis revealed that N-terminal residues from aa 6 to aa 19 in the PreS1 domain were responsible for its ER retention.…”
Section: Deletion Of Aa 25-39 In the Pres1 Domain Is A Causative Famentioning
confidence: 86%
“…Based on the analysis of a large European cohort of HBV chronically infected patients, we identified an HBV genotype A mutant with a deletion of 15 aa (aa 25‐39 in the N‐terminal PreS1 domain . Western blot analysis of the serum of the patient using HBsAg‐specific antibodies did not show truncated LHBs, presumably due to the transcomplementation from integrated HBV‐DNA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deletion variant was isolated from a patient suffering from chronic HBV infection. Although deep sequencing analysis confirmed the isolated variant as the major variant (≥99% of the quasispecies), only intact LHBs was found in the patient serum, surprisingly . This indicates that the released LHBs (viral particles and filaments) must be derived from different genetic sources.…”
mentioning
confidence: 90%
“…This source of HBsAg is relatively inaccessible without cell loss. A better understanding of differences in the composition and source of subviral particles of HBsAg derived from covalently closed circular DNA vs integrated HBV DNA will assist therapeutic strategies …”
Section: Virology Of Hepatitis B and Prospects For A Curementioning
confidence: 99%